Western political thought : from Plato to Marx - Jha, Shefali (New Delhi, 2010)
Western Political Thought: From Plato to Marx is a lucid and comprehensive account of political thought that stretches from ancient Greece to the nineteenth century. Analysing political philosophies chronologically, this book offers valuable insights into the political structures of societies across the ages, and presents a wide perspective on the various social and political ideologies. Each of the 12 chapters has boxes with excerpts from the original works by the philosophers, a comprehensive reading list and thought provoking questions on the philosophies discussed in the book.
Keywords: Political thought, Western